Monetary Policy Of The Uzbekistan And Its Improvement Ways In Implementing - Ikramovich, Ro’ziyev Zafar; Shukhratovna, Yakubova Shamsinur; Toʻlqinovich, Shodiyev Bekzod; Ibragimovna, Babayeva Lola (The journal of contemporary issues in business and government, 2021)
In world practice, the main goal of the activities of almost all central banks is to ensure the stability of national currencies and achieve price stability. The monetary policy of the central bank affects not only the money supply and interest rates, but also the overall level of economic development, that is, the well-being of every citizen in our country. Today, the world's central banks, Uzbekistan the main criterion of the Central Bank's activity is price control, inflation control. The generally accepted view today is that price management, economic education, and employment management are the necessary conditions. Prolonged periods of high inflation in a country can have dangerous consequences for the economy. This article presents scientific proposals and practical recommendations for the study and improvement of the monetary policy of the Central Bank of the Republic of Uzbekistan.